Is the maximal oxygen conspumption single best predictor or shuttle-run test? - Stojanovic, M. D.; Stojanovic, M. V.; Ostojic, S.; Fratric, F. (Serbian Journal of Sports Sciences, 2007)
The aim of the present study was to evaluate the influence of aerobic, anaerobic and strength parameters of young basketball players on the indices of shuttle run test. A sample of 26 teenage basketball players (age 15.6±1.1 years; height 188.4±8.0 cm; weight 75.0±10.6 kg) performed a battery of five tests. For each subject, maximal oxygen consumption, maximal ventilatory equivalent for oxygen and ventilatory threshold were obtained during the shuttle-run and Conconi test protocol, using a portable gas analyzer. Relative mean anaerobic power was determined during Wingate test on a cycle ergometer. Leg power and absolute leg strength were measured using standing long jump and a leg strength test was performed on an isokinetic dynamometer. The results showed that predictors significantly foresee total distance on shuttle-run test (R 2 = 0.648) in young basketball players. In the predictors system maximal oxygen consumption had the greatest individual influence, followed by ventilatory equivalent for O 2 and leg power. Obtained results indicate that total distance covered on shuttle-run test could be improved through development of anaerobic capacity or leg power besides aerobic power and/or capacity.